Conceptualising consumer regiocentrism: Examining consumers' willingness to buy products from their own region - Lee, Thomas; Cheah, Isaac; Phau, Ian; Teah, Min; Elenein, B. (Pergamon, 2016)
The key objective of the study is to address the gaps by building a theoretically based conceptual model to examine the influence of consumer regiocentrism and its moderators, and community involvement on consumers’ willingness to buy products from their own region. A mail survey of 2000 consumers from the Western Australian metropolitan area, supported four of the five proposed hypotheses. The results revealed that consumer regiocentric tendencies and community involvement positively influenced consumers’ willingness to buy products from their own region. Community involvement was also found to positively influence consumer regiocentric tendencies. Although perceived product necessity moderated the relationship between consumer regiocentrism and consumers’ willingness to buy products from their own region, perceived economic/personal threat did not moderate the relationship between consumer regiocentrism and consumers’ willingness to buy products from their own region. The study offers several implications to public policy makers as well as strategic and communication managers of regional products and brands.